2017
DOI: 10.3892/or.2017.5496
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of chromosome 3 and 4 aberrations in human uveal melanoma

Abstract: Uveal melanoma (UM) is the most common primary intraocular malignancy with a very poor prognosis. The most frequent chromosome aberration in UM is the monosomy of chromosome 3. Previously, we demonstrated that ~50% of UMs express type-I receptor for luteinizing hormone-releasing hormone (LH-RH-R). The gene encoding LH-RH-R is located in chromosome 4 (location: 4q21.2); however, the occurrence of numerical aberrations of chromosome 4 have never been studied in UM. In the present study, we investigated the abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…Notably, the gene encoding LH‐RH‐R is located on chromosome 4q21.2. Based on the chromosome index (CI) values, a correlation between the copy numbers of chromosome 3 and 4 with survival rate of UM patients was found, but the study failed to detect any correlation between LH‐RH‐R expression and chromosome aberrations . In recent years, studies have highlighted the importance of independent mutations at corresponding genetic loci in the etiology of ocular diseases, leading to the identification of several candidate genes also in UM.…”
Section: Prognostically Relevant Genetic Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the gene encoding LH‐RH‐R is located on chromosome 4q21.2. Based on the chromosome index (CI) values, a correlation between the copy numbers of chromosome 3 and 4 with survival rate of UM patients was found, but the study failed to detect any correlation between LH‐RH‐R expression and chromosome aberrations . In recent years, studies have highlighted the importance of independent mutations at corresponding genetic loci in the etiology of ocular diseases, leading to the identification of several candidate genes also in UM.…”
Section: Prognostically Relevant Genetic Changesmentioning
confidence: 99%
“…Based on the chromosome index (CI) values, a correlation between the copy numbers of chromosome 3 and 4 with survival rate of UM patients was found, but the study failed to detect any correlation between LH-RH-R expression and chromosome aberrations. 50 In recent years, studies have highlighted the importance of independent mutations at corresponding genetic loci in the etiology of ocular diseases, leading to the identification of several candidate genes also in UM. Particularly, 5 genes (BAP1, EIF1AX, GNA11, GNAQ, SF3B1) have been identified to be more frequently mutated and are often referred to as driver or key genes in UM development and progression.…”
Section: Prognostically Relevant Genetic Changesmentioning
confidence: 99%
“…There are several chromosomes in which abnormalities, losses, or gains are associated with an increased risk of metastasis. Chromosome 3 abnormalities can be useful in prognosis prediction [27]. Structural abnormalities of chromosomes 6, 8, and 11 also play a role in the uveal melanoma oncogenesis [28].…”
Section: Discussionmentioning
confidence: 99%
“… 9 In our previous study, we demonstrated aneuploidy of chromosome 4 in 70% of human UM specimens. 13 Furthermore, a correlation was found between the copy number of chromosome 3 and 4 and the survival of patients. 13 BRCA1-associated protein 1 (BAP1) is located on chromosome 3p21.1 and is thought to be a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 90%
“… 13 Furthermore, a correlation was found between the copy number of chromosome 3 and 4 and the survival of patients. 13 BRCA1-associated protein 1 (BAP1) is located on chromosome 3p21.1 and is thought to be a tumor suppressor gene. 14 Inactivating somatic mutations were found in 84% of the metastasizing UMs, implicating that BAP1 mutations occur late in the UM progression.…”
Section: Introductionmentioning
confidence: 90%